Effect of beak trimming and feather spraying with bitter taste compound on feather pecking and welfare of Muscovy ducks - Eman Hefnawy; Ahmed Sabek; Saeed El-laithy; Souad Ahmed (Scientific Reports)
Abstract The current study was conducted to compare the effect of beak trimming and feather spraying with bitter taste compound (almond oil) on feather pecking behavior and duck welfare. A total of 63 healthy male 2-weeks-old Muscovy ducklings were randomly allocated to 3 groups. The first group was the control group (no beak trimming and no feather spraying), ducks in the second group were trimmed by scissors at 3 weeks of age, and birds in the third group were sprayed with bitter almond oil weekly from the age of 3 weeks. Growth performance parameters were evaluated. Some behavioral patterns were recorded by using focal sampling. Feather condition score and serum cortisol level were evaluated. At the end of the experiment, bills were collected for histopathological examination. The results showed that beak trimming with scissors had no negative effects on Muscovy ducks’ growth performance and significantly lowered feather pecking bouts resulting in good feather conditions. Feather spraying with bitter almond oil had adverse effects on growth performance, obviously increased feather pecking resulted in deterioration of feather quality and markedly increased the level of cortisol (p < 0.001). Bill morphological analysis with hematoxylin and eosin (H&E) and S100 stains illustrated that the trimmed beak had an increase in the amount of connective tissue (scar tissue formation), numerous blood vessels, fewer nerve bundles, and no neuroma formation. In the Muscovy ducks’ sector, beak trimming with scissors at 3 weeks of age is good practice to control feather pecking and cannibalism without adverse effect on the welfare of ducks.